Downregulation of S100 Calcium Binding Protein A9 in Esophageal Squamous Cell Carcinoma. (14th December 2015) - Pawar, Harsh; Srikanth, Srinivas M.; Kashyap, Manoj Kumar; Sathe, Gajanan; Chavan, Sandip; Singal, Mukul; Manju, H. C.; Kumar, Kariyanakatte Veeraiah Veerendra; Vijayakumar, M.; Sirdeshmukh, Ravi; Pandey, Akhilesh; Prasad, T. S. Keshava; et al.
Abstract : The development of esophageal squamous cell carcinoma (ESCC) is poorly understood and the major regulatory molecules involved in the process of tumorigenesis have not yet been identified. We had previously employed a quantitative proteomic approach to identify differentially expressed proteins in ESCC tumors. A total of 238 differentially expressed proteins were identified in that study including S100 calcium binding protein A9 (S100A9) as one of the major downregulated proteins. In the present study, we carried out immunohistochemical validation of S100A9 in a large cohort of ESCC patients to determine the expression and subcellular localization of S100A9 in tumors and adjacent normal esophageal epithelia. Downregulation of S100A9 was observed in 67% (n = 192 ) of 288 different ESCC tumors, with the most dramatic downregulation observed in the poorly differentiated tumors (99/111). Expression of S100A9 was restricted to the prickle and functional layers of normal esophageal mucosa and localized predominantly in the cytoplasm and nucleus whereas virtually no expression was observed in the tumor and stromal cells. This suggests the important role that S100A9 plays in maintaining the differentiated state of epithelium and suggests that its downregulation may be associated with increased susceptibility to tumor formation.